Optimalisasi Peran ASN Kemenag Bali sebagai Agen Perubahan Lingkungan Melalui Implementasi Nilai-Nilai Ekoteologi dalam Kebijakan dan Program Kerja Formal - Ratna Mufidah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article discusses the increasingly pressing environmental crisis that demands a holistic approach that integrates spirituality and concrete action. Ecotheology presents itself as a relevant perspective, particularly for the Ministry of Religious Affairs' Civil Servants, who play a strategic role as agents of change. However, this article identifies that the role of Kemenag civil servants in Bali Province in environmental conservation is suboptimal due to the limited implementation of ecotheological values in formal policies and work programs. This gap stems from limited human resource capacity and specific knowledge of environmental issues among civil servants, which hinders the translation of spiritual values into concrete action. This paper uses qualitative methods with descriptive and ultrasound analysis approaches, as well as William Dunn's theory. This article evaluates several policy alternatives to address this issue. The analysis indicates that the most strategic and effective step is to issue formal regulations at the Bali Provincial Ministry of Religious Affairs Regional Office level, such as a Circular Letter. This regulation would provide a strong legal foundation, ensure resource allocation, and provide a clear mandate for all civil servants to integrate ecotheology into their duties and responsibilities. Thus, the discourse on environmental spirituality can be transformed into a structured and impactful work program, making the Ministry of Religion the vanguard in environmental conservation efforts in Bali.